(untitled) (International Journal of Nursing Education, 2020)
Background: Peripheral Intravenous Catheters (PIVC) are a vital tool in the delivery of patient whichare associated with number of complications including insertion difficulty, phlebitis, infiltration, occlusion,dislodgment, bloodstream infection and known to increase morbidity and mortality risk and decreased inindwelling time of PIVC. The present study was undertaken with aim to evaluate the effectiveness of apictorial flashcard regarding self-care of PIVC on its indwelling time and related complications amonginpatients.Method: A quasi experimental study using post-test only comparison group research design. Data werecollected at selected general wards of Institute of Liver and Biliary Sciences, New Delhi by non-probabilitysampling technique i.e. convenience sampling technique to select 80 subjects i.e. 40 in each experimentaland comparison group using tools such as subject’s data sheet, V.I.P. Score, Infiltration Scale, Universal PainAssessment Scale and self-developed PIVC documentation tool. Parametric and non-parametric test wereapplied to analyze the collected data using SPSS version 22.Results: Mean indwelling time of PIVC in experimental group was significantly higher (66.7 hours) ascompared to comparison group (59.4 hours) at p value of 0.038 (p<0.05). In experimental group, PIVC wereremoved on the routine basis among 77.5% of the subjects and in 22.5% of subjects PIVC was removed dueto complications. In comparison group PIVC was removed on routine basis in 57.5% of subjects whereasfor 42.5% of the subjects, the reasons for removal of PIVC was due to complications which was found tobe significant (p=0.047) at p<0.05. PIVC complications such as Phlebitis (7.5%), Infiltration (10%) andPain (15%) were present among more number of subjects in experimental group. Patients who paid hospitalexpenses out of pocket expenses had significantly higher indwelling time as compare to patients who paidthrough some insurances.Conclusion: Study concluded that Pictorial flashcard on self-care of PIVC was effective in increasing theindwelling time of PIVC and reducing the occurrence PIVC related complications.